New Fisheries-related data from the Mediterranean Sea (April 2015) - Karachle, P. K.; Basusta, A.; Basusta, N.; Bostanci, D.; Buz, K.; Girgin, H.; Vasilakopoulos, P. (Natl Centre Marine Research, 2015)
In this second Collective Article with fisheries-related data from the Mediterranean Sea we present the evaluation of bony structures in aging Barbus tauricus, otolith dimensions-body length relationships for two species (Trachinus draco and Synchiropus phaeton), information on the growth of juvenile Thunnus thynnus and Ruvettus pretiosus, weight-length relationships for three species Aulopus fiamentosus and Tylosurus acus imperialis and data on the feeding habits and reproduction of Aulopus fiamentosus.
Keywords: Body length-otolith dimension relationships; bony structures; age; growth; weigh-length relationships; diet